2011
DOI: 10.1089/jmf.2010.1152
|View full text |Cite
|
Sign up to set email alerts
|

APhellinus baumiiExtract Reduces Obesity in High-Fat Diet-Fed Mice and Absorption of Triglyceride in Lipid-Loaded Mice

Abstract: This study evaluated the anti-obesity effects of Phellinus baumii extract (PBE) in high-fat diet (HFD)-fed mice. Male 8-week-old C57BL/6 mice were randomly divided into four groups: control, normal chow diet plus vehicle; HFD-control, high-fat plus vehicle; HFD plus orlistat (Xenical(®), Roche, Basel, Switzerland) (50 mg/kg); and HFD plus PBE (500 mg/kg). PBE was administered daily by oral gavage for 12 weeks. Oral administration of PBE (500 mg/kg) significantly reduced body weight gain, hepatic lipid concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Regarding this, it has been reported that PBE shows hypolipidemic effects in the context of TG metabolism. It appears to be partly mediated by suppression of plasma TG accumulation through the inhibition of enzymes associated with intestinal TG absorption and synthesis [24]. From this, it was assumed that PBE might not have a regulatory role in cholesterol metabolism, indicating that the atherosclerosis inhibition effect of PBE is probably related to the antioxidant and anti-inflammatory activity without affecting the regulation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this, it has been reported that PBE shows hypolipidemic effects in the context of TG metabolism. It appears to be partly mediated by suppression of plasma TG accumulation through the inhibition of enzymes associated with intestinal TG absorption and synthesis [24]. From this, it was assumed that PBE might not have a regulatory role in cholesterol metabolism, indicating that the atherosclerosis inhibition effect of PBE is probably related to the antioxidant and anti-inflammatory activity without affecting the regulation of cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are not only a nutritious food, but also are a therapeutic medicine (Zjawiony, 2004;Lee et al, 2010;Wang et al, 2014). Of the wild mushrooms studied so far, P. baumii was reported for anti-obesity (Noh et al, 2011), free radical scavenging activity (Lee et al, 2010) and hypoglycemic (Hwang et al, 2005) functions.…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are valuable sources of biologically active compounds possessing anticancer [17,19], antiplatelet [25,26], antiobesity [22], and anti-inflammatory [23,26] properties. In particular, and most importantly, medicinal mushrooms represent an unlimited source of polysaccharides which are primarily modifiers of biological response where these polymers interact with the immune system to up-or downregulate specific aspects of the response of the host and this may result in various therapeutic effects [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…The mushroom, P. baumii has shown inhibitory effects on pulmonary inflammation induced by LPS in rats [23]. Noh et al [22] reported the antiobesity effect of P. baumii extract in mice. Recently, we reported the antiplatelet activity of P. baumii methanol extract [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation